Are Islamic banks more cost, revenue and profit efficient than commercial banks. (c2009) - Abi Aad, Amine (2009)
This project compares the efficiencies of commercial and Islamic banks in nine Arab countries in the Middle East. We find that Islamic banks are more efficient in terms of cost, revenue and profit than commercial Banks. This result is thoroughly depicted in small Islamic banks when compared to small commercial banks but does not hold when we compare big Islamic to big commercial banks. In Bahrain, Jordan, UAE, and Yemen commercial banks are more efficient than Islamic banks, but the results of Qatar are similar to those of the cross sectional data. We also find that after controlling for size, the data indicate that big banks are more cost and profit efficient than small banks, which is typically the case of commercial banks but not of Islamic banks. Through a semi-log regression analysis we find that the Average Return on Assets (AROA) of commercial banks is significantly affected by six independent variables while the AROA of Islamic banks is only significantly affected by three independent variables from the same pool of independent variables that we consider for both types of banks. Out of the three independent variables that are common for both types of banks, only off balance sheet lead to opposite result: it is negatively significantly related to AROA of commercial banks, and it is positively significantly related to AROA of Islamic banks. The other two variables, loan loss provisions and cost to income ratio are both negatively significantly related to A.ROA of commercial and Islamic banks.